107 Psychological safety in emergency department in-situ simulation training. (17th November 2016) - Clark, A; Buckley, A; Trippick, S
Abstract : Background: Simulation-based medical education (SBME) can present a threat to the psychological safety of learners. 1 Learners may fear embarrassment in front of their peers or supervisors. This can inhibit cognitive and behavioural flexibility in the learners, and therefore reduce learning. 2 Facilitator practices have been proposed that may increase learners' sense of psychological safety in SBME. 3 Most research into the attitudes of learners toward SBME has been in the simulation centre setting; little work has been conducted with in-situ SMBE participants, where shorter timescales can make it more difficult for facilitators to establish a safe learning environment. Methodology: Multi-professional learners at all grades taking part in our emergency department in-situ simulation exercises at UCLH are required to complete confidential pre-simulation and post-debriefing questionnaires, which are presented in a five-point Likert scale format. Our questionnaires include eight pre-sim and six post-sim questions around participants' anxiety and the concept of psychological safety. In the pre-sim questionnaire, we also ask for "three words or short phrases that describe how you feel before or during in-situ simulation training". Data is being collected between 1 April and 1 August 2016. Early results: Pre-simulation, 85% of participants described themselves as "anxious" or "nervous". 89% of medical staff, but only 40% of nursing staff, agreed that the learning environment is safe for making mistakes. Post-simulation, all professional groups were similarly (94%) likely to agree that the learning environment was safe for making mistakes. Potential impact: Our early results suggest that we cannot take learners' psychological safety for granted during in-situ simulation exercises, and there may be differences between professional groups. It may be helpful for facilitators to adopt "in-situ specific" pre-simulation practices to enhance the safety of the learning environment. We plan to develop a simple toolkit to guide the in-situ pre-simulation briefing. References: Savoldelli GL, Naik VN, Hamstra SJ, Morgan PJ. Barriers to use of simulation-based education. Can J Anaesth 2005;52 (9):944–950. Edmondson A. 1999 Psychological safety and learning behavior in work teams. Adm Sci Q 1999;44 (2):350–383. Rudolph, J, Raemer DB, Simon R. Establishing a safe container for learning in simulation. Simul Healthc 2014;9 (6):339–349.